MANAJEMEN LABA SEBAGAI VARIABEL MEDIASI PADA PENGARUH ENVIRONMENTAL, SOCIAL, GOVERNANCE TERHADAP KINERJA PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2021-2023) - Cecilia Gabriela Anastasya; Anis Chariri (Diponegoro Journal of Accounting, 2025)
The objective of this study is to examine the effect of Environmental, Social, and Governance (ESG) on firm performance, with earnings management as a mediating variable. This research aims to explore whether ESG can enhance firm performance both directly and indirectly through earnings management practices. In this study, firm performance is the dependent variable and is measured using Tobin’s Q, while ESG serves as the independent variable. Earnings management functions as the mediating variable, and firm size and return on equity (ROE) are included as control variables.The data used in this study are secondary data, consisting of annual reports and sustainability reports obtained from the official website of the Indonesia Stock Exchange. The purposive sampling method was employed to select a sample of 64 manufacturing companies listed on the Indonesia Stock Exchange during the period 2021 to 2023. To test the direct relationships between variables, this study applies multiple linear regression analysis, while the Sobel test is used to examine the mediating effect of earnings management. The results reveal that ESG has a positive and significant effect on firm performance. However, earnings management does not mediate the relationship between ESG and firm performance, as the Sobel test indicates an insignificant mediation effect. These findings suggest that the implementation of ESG directly contributes to enhancing firm performance without the necessity of relying on earnings management practices.